Flavor Characteristics of Ganpu Tea Formed During the Sun-Drying Processing and Its Antidepressant-Like Effects - Xiao, Sui; Huang, Jingyuan; Huang, Yahui; Lai, Huiqing; Zheng, Yi; Liang, Dahua; Xiao, Hang; Zhang, Xu (Frontiers in Nutrition, 2021)
Ganpu tea is a novel type of tea beverage with unique and pleasant flavor that encases Pu-erh tea leaves within an intact mandarin peel. However, to date, no holistic and detail studies on its chemical characteristics and biological activities have been reported yet. In the present study, by applying UPLC-Q-TOF and UPLC-MS technology, we systematically identified and analyzed 104 water-soluble compositions of Ganpu tea and their variation trend during the sun-drying processing. The results showed that the generation of pigments and gallic acid coincided with a dramatic decrease in catechin content, and a significant increase in alkaloid and flavonoid contents. The conversion of these compounds could co-resulted in the improvement of sensory attributes of Ganpu tea and maybe indispensable to its unique flavor. Moreover, the mice given orally with high dose of Ganpu tea (0.4 g/kg) showed a significantly reduced immobility duration as compared to that of the negative control group (p < 0.01) both in the forced swimming test and tail suspension test. Together, these results indicate that the sun-drying processing was indispensable to the formation of the unique flavor for Ganpu tea. Multiple types of compounds of Ganpu tea may collectively provide the synergistic attributes to its antidepressant-like properties.